2012
DOI: 10.3747/co.19.1298
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Deprivation Therapy in Advanced Prostate Cancer: Is Intermittent Therapy the New Standard of Care?

Abstract: Purpose: Intermittent androgen deprivation is increasingly used as an alternative to continuous life-long androgen deprivation therapy for men with advanced or recurrent prostate cancer. Recent Findings: Two recent phase III trials have clarified the benefits of intermittent therapy. The Canadian-led pr.7 trial in men with nonmetastatic disease and prostate-specific antigen recurrence after definitive local therapy showed that intermittent therapy resulted in survival equivalent to that with continuous therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…In fact, survival in two of the M1 trials (S9346 and TAP22) was worse for the IAD arm compared with the CAD arm. 7,10 Interestingly, many of the recent reviews concluded that IAD is as effective as CAD in PC [2][3][4][5][6]17 ; however, these reviews often overlooked important issues, such as NIM selection including clinically meaningful differences in survival, follow-up time too short to observe disease-specific end points, suboptimal design of mixed patient populations, and small underpowered trials.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, survival in two of the M1 trials (S9346 and TAP22) was worse for the IAD arm compared with the CAD arm. 7,10 Interestingly, many of the recent reviews concluded that IAD is as effective as CAD in PC [2][3][4][5][6]17 ; however, these reviews often overlooked important issues, such as NIM selection including clinically meaningful differences in survival, follow-up time too short to observe disease-specific end points, suboptimal design of mixed patient populations, and small underpowered trials.…”
Section: Discussionmentioning
confidence: 99%
“…The development of CRPC can take from a few months to more than ten years [3,6], after which there is a very limited number of effective treatments and patients suffer high mortality [7]. ADT is expensive and its side effects include sexual dysfunction, hot flashes, and fatigue [8]. Based on some preclinical studies, intermittent androgen suppression (IAS) is suggested as a sensible alternative to ADT [9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on some preclinical studies, intermittent androgen suppression (IAS) is suggested as a sensible alternative to ADT [9]. During off-treatment periods, patients enjoy a "vacation" from the severe side effects of ADT [8], and studies have suggested that IAS may not negatively affect the time to resistance progression or survival in comparison to ADT [10]. Consequently, IAS is selected by some patients to improve the quality of life and also hopefully to delay the progression to CRPC [4].…”
Section: Introductionmentioning
confidence: 99%
“…3), and response to the next cycle of ADT. 35 The fact that low levels of testosterone are beneficial during ADT treatment does not imply that these low levels must be continuously sustained to achieve the benefit.…”
Section: Klotz Et Almentioning
confidence: 99%